(untitled) (International Journal of Physiotherapy, 2016)
Background: Postmenopausal hypertension is the most common risk factor of cardiovascular morbidity and mortality. As the exercises training conveys benefits of the setting of secondary prevention of hypertension. High intensity interval training (HIIT) emerged as a new form of physical training and presents as therapeutic alternative to patients and health care professionals. This study aimed to investigate the effect of high intensity interval training on endothelial function in postmenopausal hypertension. Methods: Forty six mildly hypertensive postmenopausal women, their ages ranged from (45-55) years old, were randomly allocated to two groups: HIIT group (group-I; n=23) performed a high intensity interval training 3 times a week for 10 weeks at an intensity of (80-85% HR max ) for 40 minutes and control group (group-II; n=23) remains sedentary during this period. Serum nitric oxide (NO), vascular endothelial growth factor levels (VEGF) and blood pressures were measured before and after intervention. Results: A significant reduction in both systolic and diastolic blood pressure values by 9.5% and 7 % respectively, was seen after high intensity interval training which was accompanied by increase in NO and VEGF levels by 43.3% and 15.2 % respectively, while no significant change observed in the control group. Conclusion: High intensity interval training had obvious benefits in improving plasma No, VEGF concentrations and controlling hypertension in postmenopausal women.